ANALISIS KEMAMPUAN DALAM PENGEMBANGAN FILM PEMBELAJARAN MAHASISWA PENDIDIKAN FISIKA UIN WALISONGO - Edi Daenuri Anwar (Phenomenon : Jurnal Pendidikan MIPA, 2018)
The research has been conducted on the development of learning film by physics teacher candidate students in learning media courses. In this research, students make a learning film about basic physics practice is accompanied by a lecturer of media courses. The product of the learning film that has been created by the student is tested by the student's users. Assessment results include sound, music, and visualization. From the assessment results are processed by the quantitative approach and described by the results of this quantitative processing. The results show that in general subject matter consisting of a) the suitability of the subject matter with the goals formulated, b) the subject matter is easily understood, c) the subject matter corresponds to the level of the user/student ability, d) the subject matter is presented from simple to complex, and e) the subject matter delivered coherently and regularly. The five components that users say are good. While the second element of the narrative includes a) volume, b) sound intonation to facilitate understanding, c) the style of language used is very clear, d) clarity of speech and e) the language used is simple and easy to understand. Generally good except on component d) clarity of speech that gives sufficient appraisal. and the third assessment component of music consisting of a) music illustration supporting the program and b) music illustrations and sound effects are not too intrusive, these two elements are in enough categories.